2018
DOI: 10.1097/sap.0000000000001566
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Biodegradable Membrane Promote Nerve Regeneration and Functional Recovery After Sciatic Nerve Transection in Adult Rats

Abstract: The present study showed the positive effects of Mem + Cur on nerve regeneration of transected sciatic nerve in rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These markers are indicative of increased SC recruitment and promyelinating activity. As such, an increase in myelin thickness [ 34 , 40 , 41 , 66 , 69 , 70 , 76 , 80 ] and axon diameter [ 34 , 66 , 70 , 74 , 76 , 80 ] is observed with curcumin treatment. Also, of note is the proposed involvement of extracellular signal-regulated kinase (ERK) and p38 kinases [ 35 ].…”
Section: Curcumin Mechanisms Of Action and Cellular Targets In Thementioning
confidence: 99%
See 1 more Smart Citation
“…These markers are indicative of increased SC recruitment and promyelinating activity. As such, an increase in myelin thickness [ 34 , 40 , 41 , 66 , 69 , 70 , 76 , 80 ] and axon diameter [ 34 , 66 , 70 , 74 , 76 , 80 ] is observed with curcumin treatment. Also, of note is the proposed involvement of extracellular signal-regulated kinase (ERK) and p38 kinases [ 35 ].…”
Section: Curcumin Mechanisms Of Action and Cellular Targets In Thementioning
confidence: 99%
“…Some other ways of assessing nerve regeneration are by looking at nerve fibers regrowth and functional recovery. As seen in the DRG, after curcumin treatment, the number of sciatic nerve fiber increased [ 66 , 69 , 74 , 80 ] in rodent models of sciatic nerve transection, nerve crush injury, and even complete sciatic nerve amputation. The sciatic functional index (SFI) also improved in the above models [ 66 , 69 , 76 ].…”
Section: Curcumin Mechanisms Of Action and Cellular Targets In Thementioning
confidence: 99%
“…After PNI, curcumin was able to reduce cell loss [ 27 ], improve the action, potential amplitude and conduction velocity [ 28 ], improve mechanical sensitivity [ 29 ], functional assessments [ 29 , 31 , 32 , 35 ], motor and sensitive nerve conduction velocity [ 29 ], axonal regeneration [ 32 , 34 ], myelination [ 29 , 31 , 33 ], and therefore improved the diameter of nerve fibers [ 31 ], reduce reactive oxygen species [ 29 , 35 ], lipid peroxidation [ 29 ] and cell death [ 35 ], and expedite the reversal of mechanical allodynia [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…It was noted that the conduit could serve as suitable matrix for stem cell transplantation for in vivo nerve regeneration and the authors concluded that due to presence of PUAO and CS in a single conduit, cell proliferation was enhanced and showed potential to be used in vivo peripheral nerve regeneration. Moattari et al [ 163 ] reported the use of curcumin and chitosan membrane for peripheral nerve injuries. Curcumin is obtained from a plant named Curcuma which is known to have anti-inflammatory and antioxidant properties.…”
Section: Bioengineering Approaches To Regenerating Cns and Pnsmentioning
confidence: 99%